An Analytical Method for Calculating Short-Term Space Interception Probability - Wenzhe Ding; Xinhong Li; Hong Yang; Zhibin Zhang; Jiping An (International Journal of Aerospace Engineering)
For small unguided space interceptors, the interception probability is an important index to evaluate their strike capability. However, the Monte Carlo (MC) based simulation method not only consumes a lot of computation time but also theoretically lacks interpretability. In this regard, this paper proposes an analytical method that can quickly and accurately calculate the short-term space interception probability. Firstly, by considering the effect of perturbation force on spacecraft as the effect of external force acceleration, the analytical calculation formula of the short-term state error covariance propagation of space target and interceptor is deduced. Next, by projecting the state error and rotating the coordinate system, the joint error distribution of the target and the interceptor in the calculation coordinate system at the time of closest approach (TCA) is obtained. Thereby convert the calculation of the space interception probability into the integral of the 2-dimensional probability density function in the circular domain. Then, the Laplace transform and Taylor expansion are used to obtain the exact power series expression and the maximum truncation error of the integral calculation, and the analytical calculation of the short-term space interception probability is realized. Finally, the effectiveness of the proposed method is verified by a simulation example. The proposed method can directly calculate the space interception probability according to the initial state error distribution of the target and interceptor, and the whole calculation process does not contain double integral operation. The proposed method has high computational efficiency, is suitable for on-orbit calculation, and provides effective support for the rapid evaluation of the strike capability of the space interceptor.